2020
DOI: 10.1007/s10646-020-02280-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mercury on North American songbirds: effects, trends, and predictive factors

Abstract: Researchers were asked to contribute new results addressing questions about the exposure and effects of mercury (Hg) in North American songbirds, a rapidly declining group of species that is the subject of enduring interest for millions of birdwatchers, the general public and conservation scientists. Important questions to be answered include: Is Hg causing or exacerbating songbird population declines? Which North American songbirds are at most risk and in which landscapes? Are there aspects of songbird natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…They may also be more sensitive to MeHg, resulting in a higher likelihood of adverse impacts on reproductive success (Heinz et al 2009 ; Jackson et al 2011b ; Whitney and Cristol 2017 ). An increasing number of studies characterizing Hg exposure in songbirds (Passeriformes) are demonstrating that certain clades are at higher risk than others, based largely on foraging behavior, and breeding habitats (Cristol and Evers 2020 ). Generally, gleaning, flycatching, and “predatory” songbirds that breed in wetland habitats (Edmonds et al 2010 ; Jackson et al 2011a , 2015 , 2020 ; Hartman et al 2013 ; Ackerman et al 2016 ; Pacyna et al 2017 ; Ackerman et al 2019 ), including estuaries (Lane et al 2011 ; Kopec et al 2018 ; Sayers et al 2021 ), rice fields (Abeysinghe et al 2017 ; Xu et al 2024 ) and tropical evergreen forest floodplains (Sayers et al 2023 ) are at highest risk of Hg exposure, especially species that forage on predaceous arthropods such as spiders (Cristol et al 2008 ; Janssen et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also be more sensitive to MeHg, resulting in a higher likelihood of adverse impacts on reproductive success (Heinz et al 2009 ; Jackson et al 2011b ; Whitney and Cristol 2017 ). An increasing number of studies characterizing Hg exposure in songbirds (Passeriformes) are demonstrating that certain clades are at higher risk than others, based largely on foraging behavior, and breeding habitats (Cristol and Evers 2020 ). Generally, gleaning, flycatching, and “predatory” songbirds that breed in wetland habitats (Edmonds et al 2010 ; Jackson et al 2011a , 2015 , 2020 ; Hartman et al 2013 ; Ackerman et al 2016 ; Pacyna et al 2017 ; Ackerman et al 2019 ), including estuaries (Lane et al 2011 ; Kopec et al 2018 ; Sayers et al 2021 ), rice fields (Abeysinghe et al 2017 ; Xu et al 2024 ) and tropical evergreen forest floodplains (Sayers et al 2023 ) are at highest risk of Hg exposure, especially species that forage on predaceous arthropods such as spiders (Cristol et al 2008 ; Janssen et al 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fish, adverse impacts of MeHg exposure include immunological, reproductive, and behavioral impairment (Hammerschmidt et al 2002 ; Depew et al 2012a ; Carvan et al 2017 ) as well as reduced capacity for predator avoidance (Webber and Haines 2003 ). In birds, numerous studies have documented reduced reproductive success, behavioral change (e.g., reduced time incubating), and neurological problems (e.g., ataxia) (Depew et al 2012a , b ; Basu 2015 ; Ackerman et al 2016 ; Evers 2018 ; Whitney and Cristol 2017 ; Cristol and Evers 2020 ). However, many species vary in their sensitivity to MeHg toxicity - potentially based on foraging guilds and phylogeny as identified and discussed by Heinz et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…To provide examples observed in other systems: Hartman et al (2019) showed that Hg was correlated with reduced nest 'constancy' that could extend the time to fledge in tree swallows (Tachycineta bicolor); Evers et al (2008) found that elevated Hg exposure in common loons (Gavia immer) resulted in decreased incubation and reduced fledging success; Hallinger and Cristol (2011) showed that reproductive success in tree swallows was lower at a site with Hg exposure during unusually warm conditions; and Zabala et al (2021) found that great egrets (Ardea alba) experienced reduced reproductive success when Hg exposure was coupled with low food availability but not when food availability was high. Whether negative effects of sublethal Hg exposure on avian reproduction is causing or exacerbating population declines is an open question of growing importance as many songbird species have experienced population losses in recent decades (Rosenberg et al 2019;Cristol and Evers 2020).…”
Section: Effects Of Hg Exposure On Fecunditymentioning
confidence: 99%
“…Aquatic birds typically have the highest exposures to environmental Hg contamination (Ackerman et al 2016), although terrestrial birds, like riparian songbirds, may also bioaccumulate MeHg to potentially harmful levels (Cristol et al, 2008;Ackerman et al, 2019;Cristol and Evers, 2020). Within the Arctic, aquatic birds are primarily exposed to elevated levels of MeHg in pelagic environments (Provencher et al, 2014a;Braune et al, 2015;Peck et al, 2016;Burnham et al, 2018;Albert et al, 2019Albert et al, , 2021, coastal shorelines, and wetland foraging habitats (Hargreaves et al, 2011;McCloskey et al, 2013;Perkins et al, 2016;Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%